Analisis Penggunaan E Commerce Dalam Meningkatkan Usaha Mikro Kecil Menengah Di Kota Makassar Studi Kasus Omorfoo Shop - Nurjannah Nurjannah; Ratnah S (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to analyze the influence of e-commerce in improving Micro, Small and Medium Enterprises (MSMEs) in Makassar City. E-commerce has become an important tool in this digital era, providing wider market access and higher operational efficiency for MSMEs. The research method used is a quantitative approach by collecting data through questionnaires distributed to MSMEs in Makassar who have adopted e-commerce. The research results show that e-commerce significantly increases income, expands market reach, and reduces MSME operational costs. Apart from that, the use of e-commerce also contributes to increasing the competitiveness and sustainability of MSME businesses. These findings indicate that the adoption of e-commerce is an effective strategy to overcome market challenges and maximize the growth potential of MSMEs in Makassar City.